Metabolic dysfunction-associated steatotic liver disease (MASLD) impacts long-term outcomes after curative-intent surgery for hepatocellular carcinoma: original article - Uluk, Deniz; Pein, Justus; Herda, Sophia; Schliephake, Frederik; Schneider, Carolin V.; Bitar, Jude; Dreher, Katharina; Eurich, Dennis; Zhang, Ingrid W.; Schaffrath, Lukas; Auer, Timo A.; Collettini, Federico; et al. (Alimentary pharmacology & therapeutics, 2025)
Background: Curative surgery for hepatocellular carcinoma (HCC) includes liver resection (LR) and orthotopic liver transplantation (OLT). Due to the obesity epidemic, metabolic dysfunction-associated steatotic liver disease (MASLD) is a frequent HCC aetiology that often coincides with increased alcohol consumption, termed MetALD, or even alcohol-associated liver disease (ALD). Methods :Patients undergoing LR or OLT for HCC at Charité—Universitätsmedizin Berlin (2010-2020) were included in this retrospective cohort study investigating disease aetiology, time to recurrence (TTR), overall survival (OS) and CT-based body composition. Results Out of 579 patients with HCC, 417 underwent LR and 162 OLT. Tumour aetiologies were viral n = 191 (33.0%), MASLD n = 158 (27.3%), MetALD n = 51 (8.8%), ALD n = 68 (11.7%) and other/cryptogenic n = 111 (19.2%). Patients with MASLD and MetALD had more intramuscular (p < 0.001, p = 0.015) and visceral fat (both p < 0.001) than patients with non-metabolic dysfunction aetiologies. Patients with MASLD-HCC had comparable TTR (median 26 months, [95% CI: 23-31] vs. 30 months [95% CI: 4-57], p = 0.425) but shorter OS than patients with other HCC aetiologies (63 months [95% CI: 42-84] vs. 80 months [95% CI: 60-100], hazard ratio: 1.53 [95% CI: 1.050-2.229], p = 0.026) after LR. Multivariate analysis confirmed MASLD aetiology, portal vein thrombosis and MELD score ≥ 10 as independent prognostic factors for OS in LR (adjusted p = 0.021,p < 0.001,p = 0.003), even after excluding in-hospital mortality (adjusted p = 0.016,p = 0.002,p = 0.002). Causes of death were similar in MASLD and non-MASLD aetiology. Conclusions: Patients with HCC undergoing LR and meeting the new MASLD criteria have significantly shorter OS. This study provides empirical prognostic evidence for the novel MASLD/MetALD classification in a large European cohort of patients undergoing curative-intent HCC therapy.
Gesehen am 03.12.2025